The policy towards Roma in the Czech lands and Slovakia after World War II = Polityka wobec Romów na obszarze Czech i Słowacji po II wojnie światowej - Kwadrans, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper the author attempts a short description of the situation of the Roma community in Czechoslovakia, as well as in countries that were created aer the break-up, or the Czech Republic and Slovakia. The text is taken into account the historical context, demographic, political, and social functioning of minorities.
Keywords: Roma; Czechoslovakia; assimilation; velvet resolution; Romowie; Czechosłowacja; asymilacja; aksamitna rewolucja